AI in mental health - Prijatelj, Erika (Poligrafi, 2025)
Recent advancements in artificial intelligence (ai) have opened up new av-enues for mental health care, offering scalable and personalized interventions that address global shortages in clinical resources. Nevertheless, these technological innovations raise profound ethical and philosophical questions concerning the nature of human flourishing and the role of technology in healing. Grounded in Christian virtue ethics and theological anthropology, the discussion emphasizes mental health as a holistic process that integrates body, mind, and spirit within relational and moral contexts. While ai can augment clinical practice, it cannot replace the essential moral, spiritual, and relational dimensions that constitute authentic healing. instead, ai’s ethical role is to complement human presence and discernment, fostering virtue and holistic well-being rather than reducing the person to data or behavior patterns. The exploration concludes by advocating for interdisciplinary approaches, ensuring that ai integration in mental health honors human dignity and promotes a comprehensive vision of flourishing.
Keywords: artificial intelligence; celostna oskrba; Christian virtue ethics; duševno zdravje; holistic care; krščanska etika vrlin; mental health; moral character; moralni značaj; teološka antropologija; theological anthropology; umetna inteligenca